Evaluation of accuracy of fit in cast metal post fabricated with direct and indirect techniques using micro-CT - An in vitro study - Sujana Antony; Kondas Vijay Venkatesh; Dhanasekaran Sihi Vahanaan (Wolters Kluwer Medknow Publications, 2021)
Context: Accuracy of fit of cast metal posts fabricated with direct and indirect techniques. Aims: To evaluate the accuracy of fit of cast metal posts fabricated with direct and indirect techniques using micro-CT. Materials and Methods: Sixty extracted human maxillary central incisors were used. The teeth were decoronated leaving 2 mm at the cementoenamel junction. Four patterns for each tooth were made including one direct and indirect wax pattern and one direct and indirect resin pattern. In total, 240 patterns and castings were made. Each tooth was scanned using microcomputed tomography (μCT) system with a resolution of 14.5 μm. μCT analyzer Sky scanner software was used to calculate the volume of space between the post and the canals. Statistical analysis used: The student paired t-test and unpaired t-test were used to determine the significant differences between groups. Results: The overall space between the canal walls and posts made with the direct wax and resin technique had an average mean value of 1.10 mm3, whereas with the indirect technique resin and wax pattern, the average mean was 1.30 mm3 which was significant. Conclusion: Within the limitations of the study, it was found that the accuracy of fit is better in direct technique using wax pattern.